Surface nanostructuring of alkali-aluminosilicate Gorilla display glass substrates using a maskless process. (11th June 2022) - Cao, Rongtao; Zhou, Ziyu; Haghanifar, Sajad; Wu, Jingyu; Li, Ming-Jun; Tan, Susheng; Leu, Paul W; Chen, Kevin P
Abstract: This paper reports on the formation of moth-eye nanopillar structures on surfaces of alkali-aluminosilicate Gorilla glass substrates using a self-masking plasma etching method. Surface and cross-section chemical compositions studies were carried out to study the formation of the nanostructures. CF x induced polymers were shown to be the self-masking material during plasma etching. The nanostructures enhance transmission at wavelengths over 525 nm may be utilized for fluid-induced switchable haze. Additional functionalities associated with nanostructures may be realized such as self-cleaning, anti-fogging, and stain-resistance.